BIM: blockchain interface framework for the construction industry. (2nd October 2021) - Vijayeta, Malla
The Construction industry contributes a noteworthy role in the economic development of a nation and the extensive usage of Building Information Modelling in Built Environment paved a podium for information exchange and digitisation. However, owing to the constraint of sole mechanism and dearth of apprehension of truthful facts, the construction industry issues cannot be rooted out completely. Block chain technology is a contemporary regionalised record database management system which bore the backbone of the development of a Bitcoin system and has powerful performance on updating of data, information repository and security minded approach. This paper investigates the fundamental philosophies and usage of these two domains in the construction industry using literature survey. On amalgamation of these two domains, the author develops an interaction matrix throughout the Life Cycle of a Project which enables the management of data in a secure, transparent and appropriate decentralised common Information Technology environment.